EVALUATION OF THE ROLE OF REACTIVE OXYGEN SPECIES IN PMC-BASED OXIDATION SYSTEMS FOR RB21 DYE DEGRADATION - Thi Tinh, Vu; Thi Bich Viet, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2024)
This work aimed to evaluate the contribution of reactive oxygen species (ROS) in a green oxidation system based on peroxymonocarbonate (PMC) to the degradation efficiency of RB21 textile dye using ROS scavengers such as t-butanol, terephthalic acid (TA), N,N-dimethylaniline (DMA), ascorbic acid. The results showed that in reaction conditions including RB21 dye 4.63 10-2 mM (50 mg/L); HCO3– 50 mM; H2O2 100 mM; Co2+ 1.70 10-3 mM (0.1 mg/L), the RB21degradation efficiency reached 90% after 180 minutes of which the contribution percentage of CO3•– radicals was the most important, 98.2%, while •OH and other ROS hardly contributed to the degradation process of RB21 dye. Moreover, the kinetic study results on the reaction between CO3•– and its scavenger, DMA, as well as between •OH and its scavenger, TA, indicated that the concentrations of  and •OH in the PMC system composed of HCO3– 50 mM, H2O2 100 mM, and Co2+ 1.70 10-3 mM were 2.35.10-13 M and 1.50.10-16 M, respectively.